2018
DOI: 10.1016/j.yebeh.2018.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Language mapping using electrocorticography versus stereoelectroencephalography: A case series

Abstract: Direct electrical stimulation (DES) is sometimes used in epilepsy surgery to identify areas that may result in language deficits if resected. Extraoperative language mapping is usually performed using electrocorticography (ECOG) - grids and strip electrodes; however, given the better safety profile of stereoelectroencephalogaphy (SEEG), it would be desirable to determine if mapping using SEEG is also effective. We report a case series of fifteen patients that underwent language mapping with either ECOG (5), SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This method relies on a 3D representation of the epileptogenic zone (EZ) (Kahane et al, 2006), later conceptualized as an epileptogenic network (Bartolomei et al, 2017). The relevance of sEEG for language mapping using ECS has been questioned by some users of ECS with subdural grids (Young et al, 2018). These authors have argued that in contrast to sEEG, subdural grids or strips of circular electrodes placed at the surface of the brain, offered a wider and denser spatial coverage of the cortical surface in a given anatomical area.…”
Section: Historical Considerations Of Ecsmentioning
confidence: 99%
“…This method relies on a 3D representation of the epileptogenic zone (EZ) (Kahane et al, 2006), later conceptualized as an epileptogenic network (Bartolomei et al, 2017). The relevance of sEEG for language mapping using ECS has been questioned by some users of ECS with subdural grids (Young et al, 2018). These authors have argued that in contrast to sEEG, subdural grids or strips of circular electrodes placed at the surface of the brain, offered a wider and denser spatial coverage of the cortical surface in a given anatomical area.…”
Section: Historical Considerations Of Ecsmentioning
confidence: 99%
“…2,11 Direct electrical stimulation for mapping of eloquent cortex is usually performed using ECOG; however, there is some evidence to suggest that language mapping with SEEG gives concordant results to ECOG. 12…”
mentioning
confidence: 99%
“…One case study of extraoperative SEEG language mapping vs. intraoperative mapping showed discordant results (41). In a more recent case series, Young et al demonstrated that SEEG may be equally as efficacious as ECoG in mapping language areas among a small cohort of 15 patients, resulting in safe resection or ablation in six cases (42). These findings are part of a small number of studies investigating the efficacy of SEEG ESM of language functions.…”
Section: Primary Clinical Outcome Metrics Derived From Seeg Stimulatimentioning
confidence: 99%